(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The article includes the informative content concerning one of the issues of the pragmatics-distinction between implicatures and entailments. Pragmatics as well as its object are being thoroughly studied because of their importance. The aim of this paper is to define certain distinguishing characteristics of entailments, presuppositions, and implicatures. The aim is to investigate the essence and role of these various forms of inferencing in a conversational setting. Various kinds of samples are given in order to show differences and clarify the borders of notions.